Evaluasi Tingkat Penerimaan Sistem Manajemen Aset Menggunakan Metode HOT-FIT - Muhammad Amiruddien; Aris Puji Widodo; R Rizal Isnanto (JSINBIS (Jurnal Sistem Informasi Bisnis), 2021)
The development of the institution will be directly proportional to the development of the number and types of assets it owns. The growing number and type of assets owned by an institution will have an impact on increasingly difficult management. In asset management, Diponegoro University has developed an Sistem Informasi Manajemen Aset Terpadu (SIMASET). SIMASET needs to be evaluated to find out its shortcomings and can be input for further development. This study aims to determine the factors that influence the level of acceptance and net benefits received by users from the application of SIMASET using the Human-Organization-Technology (HOT-Fit) method. This study begins with designing hypotheses, determining the sample of respondents, filling out questionnaires, and ending with questionnaire data analysis. There are 20 hypotheses tested regarding the relationship between technology, human and organizational constructs in the HOT-Fit method. The Partial Least Squares-Structural Equation Modeling (PLS-SEM) method in the Smart-PLS 3.0 application is used to analyze the questionnaire data that has been filled out by SIMASET direct users. The results showed that the net benefits of implementing SIMASET were increasing effectiveness, helping decision making, reducing errors and facilitating communication. In addition, it can be seen that SIMASET's shortcomings lie in the quality of information and service quality because they have no significant effect on system use and user satisfaction. SIMASET acceptance rate of 51.6% or moderate taken from the R-square value of net benefits.